Immunocytochemistry as a Diagnostic Procedure of Pleural Mesothelioma - Trimurtini, Asih; Astuti, Triwahju; Yudhanto, Hendy Setyo; Erawati, Dini Rachma (Malang Respiratory Journal, 2020)
Background: Mesothelioma is a primary malignant tumor arising from the mesothelial surface of the pleura, peritoneal, tunica vaginalis, and pericardium. Most cases of mesothelioma originate from the pleura. Most patients have a history of asbestos exposure. A common diagnostic problem is distinguishing mesothelioma from adenocarcinoma since both tumors invade the pleura. Immunocytochemistry of calretinin and TTF-1 can be used to establish the diagnosis of mesothelioma.Case: Male, 56 years old presented with chest pain, shortness of breath, cough, and weight loss since 5 months before hospitalization. The patient had a history of occupational exposure to asbestos for 30 years. The movement and breath sounds were decreased as well as dull upon percussion at the right chest. A chest X-ray revealed a right lung tumor with pleural effusion. Thorax CT scan suggested pleural mass in right hemithorax, infiltration to intercostal muscles, and destruction of the 7th right rib, right perihilar lymphadenopathy, right pleural effusion, and liver nodules according to mesothelioma T4N1M1 Stage IV. Infiltrative stenting of the right and inferior lobe of the right lung, infiltrative and obstructive stenting of the medius lobe suggestive of a chronic malignancy and inflammation were found on FOB. Cytologic examination of pleural fluid, sputum, and Washing-and-brushing of FOB were a class II (no malignant cells). USG-guided transthoracic FNAB revealed adenocarcinoma with differential diagnosis of mesothelioma. Immunocytochemistry with calretinin showed positive results and TTF-1 showed a negative result. These confirmed the diagnosis of pleural mesothelioma T4N1M1 Stage IV. The patient showed a stable response from carboplatin/gemcitabine treatment.Keyword : Mesothelioma, Immunocytochemistry, TTF-1, Calrenitin